Odpowiedzi

2010-04-13T10:39:51+02:00
2,5+2*1/2= 2,5 + 1 = 3,5
1,2-(0,1+2/5)= 1,2 - (0,1 + 0,4) = 1,2- 0,5 = 0,7
0,4*1/4+7= 0,4 * 0,25 + 7 = 7,1
4,4:4+1/4= 1,1 + 0,25 = 1,35
2/5:(2*0,5)= 0,4 : 1 = 0,4
2/3*6:1/4= 4 * 4 = 16
(0,5+1/2)*2= 1 * 2 = 2
7,2-1/8*24= 7,2 - 3 = 4,2
2010-04-13T10:43:59+02:00
2,5+2*1/2=2,5+1=3,5
1,2-(0,1+2/5)=1,2-(1/10+4/10)=12/10-5/10=7/10
0,4*1/4+7=4/10*1/4+7=1/10+7=7,1
4,4:4+1/4=1,1+1/4=1,1+0,25=1,35
2/5:(2*0,5)=2/5:1=0,4
2/3*6:1/4=4*4=16
(0,5+1/2)*2=1*2=2
7,2-1/8*24=7,2-0,125*25=7,2-3=4,2
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-04-13T11:19:52+02:00
3,5
0,7
7,1
1,35
0,4
16
2
4,2

To jest w kolejności. Mam nadzieję, że pomogłam. Pozdrawiam.
1 5 1